Cyclodextrin Stabilized Freeze-Dried Silica/Chitosan Nanoparticles for Improved Terconazole Ocular Bioavailability - Nada Zaghloul; Nada M. El Hoffy; Azza A. Mahmoud; Nermeen A. Elkasabgy (MDPI AG, 2022)
This research assesses the beneficial effects of loading terconazole, a poorly water-soluble antifungal drug in silica/chitosan nanoparticles (SCNs) for ocular delivery. Nanoparticles were fabricated by the simple mixing of tetraethyl ortho silicate (TEOS) and chitosan HCl as sources of silica and nitrogen, respectively, along with alcoholic drug solution in different concentrations. Freeze-dried nanoparticles were fabricated using cyclodextrins as cryoprotectants. SCNs were assessed for their particle size, PDI, yield, drug loading and in vitro release studies. A 23.31 full factorial experimental design was constructed to optimize the prepared SCNs. DSC, XRD, FTIR, in addition to morphological scanning were performed on the optimized nanoparticles followed by an investigation of their pharmacokinetic parameters after topical ocular application in male Albino rabbits. The results reveal that increasing the water content in the preparations causes an increase in the yield and size of nanoparticles. On the other hand, increasing the TEOS content in the preparations, caused a decrease in the yield and size of nanoparticles. The optimized formulation possessed excellent mucoadhesive properties with potential safety concerning the investigated rabbit eye tissues. The higher Cmax and AUC0-24 values coupled with a longer tmax value compared to the drug suspension in the rabbits' eyes indicated the potential of SCNs as promising ocular carriers for poorly water-soluble drugs, such as terconazole.